Nanostructured Lipid Carriers for Targeting Central Nervous System: Recent Advancements - Ojha, Smriti; Mishra, Sudhanshu (Micro and Nanosystems, 2023)
Background: Lipid nanocarriers (NLCs) have undergone significant research over the past two decades to determine how well they target drugs to important parts of the human body, such as the central nervous system (CNS), the heart region, tumor cells, etc. Objective: The objective of this review paper was to review and critically summarize recent progress in NLC for targeting CNS. Methods: The structure, classification, elements, and numerous preparation techniques have been carefully outlined in this paper, along with their benefits and drawbacks, as demonstrated by several research investigations. Results: This review focuses on recent developments in NLCs for brain targeting of bioactives with special attention to their surface modifications, formulation aspects, pharmacokinetic behavior, and effectiveness for treating a variety of brain disorders. Conclusion: Poorly water-soluble bioactive substances’ physicochemical properties and behavior, such as aqueous dispersibility and oral bioavailability, can be greatly improved using lipid nanocarriers. Due to the brain's complicated structure and numerous protective systems, drug distribution to the brain has remained a difficult problem for scientists. The employment of an appropriate nanocarrier technology and an alternate drug delivery method, such as nose-to-brain drug delivery, could overcome the problem of brain targeting and increase the therapeutic effectiveness of CNS-acting medications. The pharmaceutical business has recently transformed various innovative drug delivery methods that address the drawbacks of conventional drug delivery systems and offer a good benefit-to-risk ratio.
Keywords: drug delivery